Evaluation of the effects of PHAST training and community health interventions on the hygiene behaviour of children and women to prevent diarrhoeal diseases- in the Locality of Rashad/ South Kordofan/ Republic of Sudan - Annett Weidner (2010)
Access to drinking water and improved sanitation are a fundamental need for health of all people. Diarrhoea due to infection is widespread throughout the developing world. It is estimated that 90.0% of all cases of diarrhoea can be attributed to three major causes: inadequate sanitation, poor hygiene and unclean water. Each year approximately 2.2 million people die from diarrhoeal diseases worldwide, 90.0% are children under 5 years of age. (WHO, 2000) Besides the mentioned causes of diarrhoeal diseases and its abolishment, knowledge and attitude about hygiene and sanitation and the practice of good hygiene behaviour in children and women is needed to reduce diarrhoeal infections and moreover to prevent getting it. The effects of the undertaken PHAST training related to gained knowledge, attitude and practice (KAP) were investigated by using a quantitative approach in order to prove change in hygiene behaviour according to KAP model. Health indicators in terms of quantitative figures were analyzed. Interviews, observations and tests were done with 118 participants whereby the main target group of the study was based on 70 children and 30 women from three villages in Rashad locality. The tests examined their knowledge in good/bad behaviour related to sanitation, hand washing, water, food preparing and handling as well as in modes of transmission and preventive activities, whereas the passive observation their attitude and practice investigated. It was found a significant better knowledge in all items in children and women who attended the PHAST training (cases) compared to those who have never attended (controls). However changes in their attitude towards better hygiene and sanitation and their performances could not be evidence based confirmed at the end, neither in cases nor in controls. However during the time of observation it could be found that health facilities and staff in the villages and compounds tend to practice good hygienic activities. In summary an association between the undertaken PHAST training and knowledge could be found but the change in hygiene behaviour according to the KAP model could not be proven. The PHAST training and other health interventions tend to prevent people from getting diarrhoeal diseases however valid data to prove it were not available in this region.
Keywords: PHAST training; diarrhoeal diseases; hygiene behaviour; water; sanitation